Taxonomic Revision of Endemic Rodents (Zoological Archives: An International Journal, 2026)
Rodents are the most species-rich mammalian order, with approximately 2,500 described species constituting 40% of allmammals, yet island and archipelago endemic rodent faunas remain poorly characterised taxonomically, with unresolvedspecies boundaries, incorrect synonymies, and undescribed species -- all with direct consequences for IUCN Red Listassessments and conservation prioritisation. This study conducted a comprehensive taxonomic revision of endemicrodents from 28 island and mountain archipelago systems across Europe, Asia, and Africa, applying integrativetaxonomy combining COI and cytochrome b DNA barcoding (2,840 sequences from 284 museum specimens and 240fresh-collected individuals), geometric morphometrics of 18 cranial landmarks (1,284 museum specimens), and externalmorphometric measurements to 84 nominal species representing 12 genera. The integrative approach confirmed 64 ofthe 84 nominal species as valid, synonymised 12 nominal species (reducing to 6 valid species in 4 revised speciesgroups), resurrected 4 synonymised names as valid species, and formally described 8 species new to science. Netresult: 72 valid species from the 84 nominal -- a 14.3% reduction through synonymy offset by 19.0% increase fromresurrections and new species. Geographic range reassessments based on revised taxonomy changed the IUCN RedList category of 18 species: 8 species moved from Least Concern to Vulnerable or Endangered (their ranges are smallerthan previously recognised), 6 from Endangered to Least Concern (their ranges are larger through synonymydissolution), and 4 new species require immediate Endangered or Critically Endangered assessment given theirrestricted island endemism. These revisions demonstrate the direct conservation impact of taxonomic research and theurgent need for taxonomy-conservation integration in island rodent management.